2007
DOI: 10.1038/nn1904
|View full text |Cite
|
Sign up to set email alerts
|

RIM1 confers sustained activity and neurotransmitter vesicle anchoring to presynaptic Ca2+ channels

Abstract: The molecular organization of presynaptic active zones is important for the neurotransmitter release that is triggered by depolarization-induced Ca2+ influx. Here, we demonstrate a previously unknown interaction between two components of the presynaptic active zone, RIM1 and voltage-dependent Ca2+ channels (VDCCs), that controls neurotransmitter release in mammalian neurons. RIM1 associated with VDCC beta-subunits via its C terminus to markedly suppress voltage-dependent inactivation among different neuronal V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
260
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(275 citation statements)
references
References 51 publications
15
260
0
Order By: Relevance
“…RIM1␣, however, interacts directly with Ca 2ϩ -binding proteins such as Munc13-1 and synaptotagmin 1 (19, 20, 32). Moreover, RIM1␣ interacts directly or indirectly with presynaptic VDCCs, thereby regulating the function and/or the physical location of VDCCs in relation to the release site (20,21,33). Thus, RIM1␣ might orchestrate presynaptic signaling complexes and enable compartmentalized signal transduction within presynaptic scaffolds by bringing VDCCs, Ca 2ϩ sensors, and the vesicular fusion machinery into close proximity allowing for activity-dependent and persistent modifications in the vesicular release probability.…”
Section: Discussionmentioning
confidence: 99%
“…RIM1␣, however, interacts directly with Ca 2ϩ -binding proteins such as Munc13-1 and synaptotagmin 1 (19, 20, 32). Moreover, RIM1␣ interacts directly or indirectly with presynaptic VDCCs, thereby regulating the function and/or the physical location of VDCCs in relation to the release site (20,21,33). Thus, RIM1␣ might orchestrate presynaptic signaling complexes and enable compartmentalized signal transduction within presynaptic scaffolds by bringing VDCCs, Ca 2ϩ sensors, and the vesicular fusion machinery into close proximity allowing for activity-dependent and persistent modifications in the vesicular release probability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that RIM1 anchors SNAREs close to calcium channels by C-terminal binding to the channel β subunit, thereby prolonging calcium influx by inhibiting channel inactivation. 128 This effect was seen in P/Q-type channels as well as N-and R-type channels, and suggests that RIM may be an important regulator of synaptic calcium channel function.…”
Section: Functional Interactions Of Presynaptic Calcium Channels Withmentioning
confidence: 97%
“…Gene deletion experiments (Table S1) showed that RIMs are essential for multiple aspects of neurotransmitter release (4, 6-10) and for presynaptic short-and long-term plasticity (4, 6, 11-13). However, how different RIM isoforms contribute to neurotransmitter release is unclear.Recent studies revealed that RIMs regulate presynaptic Ca 2+ channels via two independent mechanisms, namely by recruiting Ca 2+ channels to active zones (14) and by modulating Ca 2+ -channel opening times (15,16). The first activity is mediated by a tripartite complex of RIMs, RIM-BPs, and Ca 2+ channels in which the RIM PDZ domains directly bind to the C-termini of N-and P/Q-type Ca 2+ channels, the RIM PxxP-sequences bind to RIM-BPs, and RIM-BPs, in turn, directly bind to the C-termini of Ca 2+ channels (14, 17, 18).…”
mentioning
confidence: 99%
“…The first activity is mediated by a tripartite complex of RIMs, RIM-BPs, and Ca 2+ channels in which the RIM PDZ domains directly bind to the C-termini of N-and P/Q-type Ca 2+ channels, the RIM PxxP-sequences bind to RIM-BPs, and RIM-BPs, in turn, directly bind to the C-termini of Ca 2+ channels (14,17,18). The second activity is mediated by the RIM C 2 B-domain, possibly by binding to β4 subunits of Ca 2+ channels (15,16). However, the relative contributions of different RIM isoforms and of their interactions with Ca 2+ channels are unknown.…”
mentioning
confidence: 99%